Solar lighting project for remote schools / Nur Azfahani Ahmad - Ahmad, Nur Azfahani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2022)
Researchers from Faculty of Architecture, Planning and Surveying, Universiti Teknologi MARA (UiTM) Perak Branch have initiated a community-based approach project that helps rural schools in Perak to harvest solar energy for lighting purposes. This project involved three schools in Per-ak and was led by Sr Dr Nur Azfahani Ahmad with an aim to provide a sustainable power supply to generate lighting for the targeted schools. The main purpose was to assess the effectiveness of solar electrification in rural schools with the involvement of local communities. This project was funded by the FRGS grant, and has officially started since March 2019 until March 2021. This project witnessed the involvement of 10 researchers and 5 postgraduate students from the Faculty of Architecture, Planning and Surveying, UiTM Perak branch.